1995
DOI: 10.1093/clinids/20.supplement_1.s91
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Infection and Genital Warts: Update on Epidemiology and Treatment

Abstract: The treatment of genital warts remains frustrating since it is often painful, expensive, and unsuccessful. Moreover, little is known about the infectivity and natural history of exophytic genital warts or subclinical genital infection with human papillomavirus. The traditional goals of therapy for sexually transmitted diseases--eradication of infection, elimination of symptoms, prevention of long-term sequelae, and interruption of transmission--are currently not attainable for or applicable to genital warts. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0
16

Year Published

1997
1997
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(82 citation statements)
references
References 40 publications
3
63
0
16
Order By: Relevance
“…Data could not be retrieved for 10 published studies [14][15][16][17][18][19][20][21][22][23][24] and 1 research group 25 declined to take part in the collaboration. Of the studies identified, original data were available from 25,6, and all had information on reproductive factors and were therefore included in the present collaborative reanalysis (Table I).…”
Section: Resultsmentioning
confidence: 99%
“…Data could not be retrieved for 10 published studies [14][15][16][17][18][19][20][21][22][23][24] and 1 research group 25 declined to take part in the collaboration. Of the studies identified, original data were available from 25,6, and all had information on reproductive factors and were therefore included in the present collaborative reanalysis (Table I).…”
Section: Resultsmentioning
confidence: 99%
“…Эти препараты необходимо наносить не один раз в условиях клиники, кроме того, при их приме-нении часто возникают местные воспалительные реакции, такие как эритема, эрозии и даже язвен-ные дефекты. Ни один из этих методов не обеспечи-вает предсказуемое, полноценное, комфортное уда-ление бородавок с низким процентом рецидивов [15,16].…”
Section: клинические проявления и терапия пвиunclassified
“…Хотя хирургическое иссечение, электрокоагуля-ция и лазерная вапоризация могут использоваться для быстрого удаления бородавок, эти методы явля-ются болезненными, агрессивными и сопровожда-ются частыми рецидивами (например, рецидив от-мечен у 9-72% пациентов после лазерной абляции) [15].…”
Section: клинические проявления и терапия пвиunclassified
See 2 more Smart Citations